Fundamental analysis of semiconductor-metal transition in indium-doped zinc oxide using carrier concentration and current-voltage measurements. - Saw , Kim Guan (Universiti Sains Malaysia, 2017)

(untitled)
Transparent conducting oxides in the form of metal-doped ZnO thin films have important applications in optoelectronic devices. In this work, In-doped ZnO thin films were synthesized by magnetron sputtering using targets with different wt% (1 - 7%) of In20~ at a substrate temperature of 150°C on quartz and Si substrates.